2017
DOI: 10.1021/acsomega.7b00900
|View full text |Cite
|
Sign up to set email alerts
|

Winged-Cone Conformation in Hexa-p-tert-butylcalix[6]arene Driven by the Unusually Strong Guest Encapsulation

Abstract: Hexa- p - tert -butylcalix[6]arene (1) is believed to adopt a winged conformation in a solution, featured by four phenyl rings perpendicular to the calix basis and two others at 1,4-positions lying down. However, there is some controversy on the occurrence of this conformation because it has never been found in the solid state of calix[6]arenes, regardless of the substitution pattern at lower and upper rims. Here, we have observed the winged-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…Here, only the structures with the pinched-cone conformation are discussed. The crystal structures with winged-cone (Martins et al, 2017) and 1,2,3-alternate conformations (Wolfgong et al, 1996) have been reported previously. To describe clearly the interactions of the solvent molecules with the calixarene structure, the phenyl rings of the calixarene were labelled as A-and B-type rings (Fig.…”
Section: Crystal Structuresmentioning
confidence: 83%
See 1 more Smart Citation
“…Here, only the structures with the pinched-cone conformation are discussed. The crystal structures with winged-cone (Martins et al, 2017) and 1,2,3-alternate conformations (Wolfgong et al, 1996) have been reported previously. To describe clearly the interactions of the solvent molecules with the calixarene structure, the phenyl rings of the calixarene were labelled as A-and B-type rings (Fig.…”
Section: Crystal Structuresmentioning
confidence: 83%
“…acetone or dimethyl sulfoxide (DMSO)] can disrupt the intramolecular hydrogen bonding, the calixarene assumes a distorted 1,2,3-alternate conformation. However, pyridine (Malinska, 2021) and DMSO (Martins et al, 2017), which are both molecules that can form hydrogen bonds, crystallize with p-tert-butylcalix[6]arene (TBC6) in a winged-cone conformation. This conformation exists only in the metastable crystal structure at room temperature, and dissolves to form crystal structures with lower host-guest ratios or pinched-cone conformations.…”
Section: Introductionmentioning
confidence: 99%
“…Different conformations were also suggested by Molins et al; i.e., winged conformations that feature four benzene rings oriented perpendicularly to the molecular base, with the two at the 1,4-positions lying entirely flat, whereas the 1,2,3-alternating conformation has three hydroxyl groups in the upper-rim and the rest of the hydroxyl groups in the lower-rim. Interestingly, low-temperature solution NMR spectroscopy identified the predominant conformation to be the winged cone . The energy differences between the winged-cone and the 1,2,3-alternating and basic conformations of p - tert -butylcalix­[6]­arene (TBC6, Scheme ) are 50 and 66 kJ mol –1 , respectively .…”
Section: Introductionmentioning
confidence: 99%
“…The energy differences between the winged-cone and the 1,2,3-alternating and basic conformations of p - tert -butylcalix­[6]­arene (TBC6, Scheme ) are 50 and 66 kJ mol –1 , respectively . The crystal formed with dimethyl sulfoxide (DMSO) was found to have a 1,2,3-alternating conformation, and new structures with a winged-cone conformations were crystallized recently with DMSO, dimethylformamide (DMF), and pyridine . The latter one have a layered structure with alternating solvent and TBC6 layers.…”
Section: Introductionmentioning
confidence: 99%
“…Their versatility is in part associated with possible functionalization in the upper and lower rims, increasing the selectivity for specific guests (Atwood et al, 2002;Martins et al, 2016). Likewise, methylene bridges enable different conformations of calix [n]arenes, resulting in the possibility of a wide range of guest molecules being included (Ř ezanková et al, 2017;Martins et al, 2017). Furthermore, calix[n]arenes show several biological properties, such as antiviral (Motornaya, et al, 2006), anticancer (Dings et al, 2012;Pelizzaro-Rocha et al, 2013) and antimicrobials (Mourer et al, 2006;Lamartine et al, 2002).…”
Section: Introductionmentioning
confidence: 99%